Construction and Immunogenicity Testing of Salmonella, STM1 Vaccine Vector Expressing HIV-1 Antigen - Endang Winiati Bachtiar; Peter Smooker; Peter J Coloe (Universitas Gadjah Mada, 2009)
Objective of this study: to determine the ability of Salmonella enterica serovar Typhimurium STM1 as a delivery vehicle for the HIV p24 gene and HIV env gene. The STM1 delivery HIV-p24 vaccination was carried out in the form of a recombinant or a DNA vaccine whereas only a DNA vaccine was used for HIV env. Naked DNA vaccination was also tested and immune responses were evaluated following immunisation in mouse model. Results: vaccination cellular immune responses induced by recombinant p24 STM1 (STM1/pHly-p24) were greater than those elicited by the p24 DNA vaccine in STM1 (STM1/VR-p24), (but statistically not significance) than those induced by oral vaccination. However, IgA responses induced by oral vaccination with either a recombinant or DNA vaccine of p24 in STM1 are higher than those induced by IP vaccination. Conclusions: This result confirms other studies that Salmonella was able to deliver HIV antigens to the immune system and induced specific immune responses to the HIV antigen.